ANALISIS KEMAMPUAN MEMBACA PERMULAAN PADA ANAK FASE A SEBAGAI FONDASI MEMBANGUN LITERASI NUMERASI: STUDI ETNOGRAFI DI SD NEGERI SARIREJO 1 - Arnita, Sinta; Purnamasari , Iin; Rofian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the suboptimal reading skills of phase A children. This is evidenced by the results of the education report card of SD Negeri Sarirejo 1 in 2024, where children's literacy and numeracy skills in several aspects have decreased scores from last year. This study used a qualitative approach with ethnographic methods. Data collection used observation, interview and documentation techniques. The results showed that (1) children in phase A of SD Negeri Sarirejo 1 still experience difficulties, such as: mispronouncing words, spelling repeatedly, difficulty combining consonant letters such as